Gaya Komunikasi Orang Tua Melalui Bahasa Verbal dalam Membangun Motivasi Berprestasi Anak - Eva Evelina Hotmauli Sihombing; Yanti Tayo; Rastri Kusumaningrum (KOMVERSAL, 2025)
This research is motivated by the importance of appropriate and effective parental communication styles through verbal language in building achievement motivation in children. The focus of this research is how communication styles in verbal language are applied by parents of SDN Gunung Putri 05 students, with the aim of identifying and analyzing each parent's communication style and its impact on children's achievement. The method used is descriptive study through observation, in-depth interviews, and document analysis for data collection. The research results show that choosing the right communication style according to the child's needs greatly influences how the message is conveyed well, so that it can increase the child's motivation to achieve achievements, both in academic and non-academic fields, according to each child's interests and talents happily without coercion. In conclusion, the right communication style from parents can encourage children to be more motivated to achieve achievements.